Multi-omics profiling of dairy cattle oxidative stress identifies hindgut-derived Phascolarctobacterium succinatutens exhibiting antioxidant activity - Duo Gao; Yimin Zhuang; Shuai Liu; Boyan Ma; Yiming Xu; Hongxing Zhang; Yiliyaer Nuermaimaiti; Tianyu Chen; Guobin Hou; Wenli Guo; Jingtao You; Zhiyu Huang; et al. (npj Biofilms and Microbiomes)
Abstract An imbalance between oxidative and antioxidant processes in the host can lead to excessive oxidation, a condition known as oxidative stress (OS). Although changes in the hindgut microbiota have been frequently linked to OS, the specific microbial and metabolic underpinnings of this association remain unclear. In this study, we enrolled 81 postpartum Holstein cows and stratified them into high oxidative stress (HOS, n = 9) and low oxidative stress (LOS, n = 9) groups based on the oxidative stress index (OSi). Using a multi-omics approach, we performed 16S rRNA gene sequencing to evaluate microbial diversity, conducted metagenomic analysis to identify functional bacteria, and utilized untargeted metabolomics to profile serum metabolites. Our analyses revealed elevated levels of kynurenine, formyl-5-hydroxykynurenamine, and 5-hydroxyindole-3-acetic acid in LOS dairy cows. Additionally, the LOS cows had a higher abundance of short-chain fatty acids (SCFAs)-producing bacteria, including Bacteroidetes bacterium, Paludibacter propionicigenes, and Phascolarctobacterium succinatutens (P. succinatutens), which were negatively correlated with OSi. To explore the potential role of these bacteria in mitigating OS, we administered P. succinatutens (108 cfu/day for 14 days) to C57BL/6 J mice (n = 10). Oral administration of P. succinatutens significantly increased serum total antioxidant capacity, decreased total oxidants, and reduced OSi in mice. Moreover, this treatment promoted activation of the Nrf2-Keap1 antioxidant pathway, significantly enhancing the enzymatic activities of GSH-Px and SOD, as well as the concentrations of acetate and propionate in the colon. In conclusion, our findings suggest that systemic tryptophan metabolism and disordered SCFAs production are concurrent factors influenced by hindgut microbiota and associated with OS development. Modulating the hindgut microbiota, particularly by introducing specific SCFAs-producing bacteria, could be a promising strategy for combating OS.